Analysis of Elementary School Teacher Readiness in Implementing the Independent Curriculum in Gorontalo City - Gamar Abdullah; Hendrayanto Hendrayanto (PT. Anagata Sembagi Education, 2024)
This research aims to find out how prepared teachers are in implementing the independent curriculum in elementary schools (SD) in Gorontalo City. The research method used in this research is descriptive research with a qualitative approach. This research was conducted in several elementary schools (SD) in Gorontalo City, including SDN 96 Kota Utara, SDN 29 Kota Selatan, SDN 75 Kota Tengah, SDN 02 Kota Barat, SDN 8 Kota Barat, SDN 42 Hulonthalangi and SDN No. 57 East City. The data collection technique used in this research was conducting in-depth interviews. The research analyzed the readiness of elementary school teachers in implementing the independent curriculum using 6 indicators, namely (1) understanding of the curriculum structure, (2) readiness of learning plans, (3) readiness of the learning process, (4) readiness of teaching material modules, (5) readiness of facilities and infrastructure, 6) readiness for learning assessment. Based on the results of the research that has been conducted, it can be concluded that the readiness of teachers in implementing the independent curriculum in elementary schools in Gorontalo City based on six indicators shows that teachers in Gorontalo City are still not fully ready to implement the independent curriculum. Some teachers still lack understanding regarding the structure of the independent curriculum and admit that they still need training, especially regarding the implementation of the independent curriculum in learning, such as developing teaching modules, learning assessments, implementing the Ancasila student profile program and utilizing PMM. Apart from that, teachers admit that they still have difficulty accessing textbooks used in implementing the independent curriculum. However, in general, school infrastructure, including the internet, is very adequate in supporting the implementation of the independent curriculum in elementary schools in Gorontalo City.